A uniqueness theorem for inverse nodal problem - Koyunbakan, Hikmet; Panakhov, Etibar S. (Taylor & Francis Ltd, 2007)
In this article, it is found that the asymptotic formulas for nodal points and nodal length for the differential operators having singularity type 1/(4 sin(2)x) at the points 0 and pi, it is shown that the potential function can be determined from the positions of the nodes for the eigenfunctions.
Keywords: Sturm-Liouville problem; eigenfunction; nodal point